(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Technological solutions allowing the increase of the technological efficiency of anaerobic methods of wastewater treatment are still under investigation. The weaknesses of these solutions can be limited by the use of active fillings. As the capability of retaining microorganisms will act as biofilm factor influencing the performance of this reactor. The aim of the present study was to determine the impact of fixed film reactor active filling on the effectiveness of anaerobic treatment of sugar-industry effluent, the production efficiency and the qualitative composition of the biogas produced. The effluent was analyzed with varying Organic Loading Rate (OLR) The OLR increased from 0.031kgCOD/m3/day to 0.288kg COD/m3/day. With an average value of Volatile Fatty Acid (VFA) of The Volatile Fatty Acid was at the maximum of 54mg/l to 24mg/l was calculated by distillation method with five sets off COD concentrations. The maximum COD removal efficiency of 86% along with production of 0.048m3/kgCOD of biogas at 3 days Hydraulic Retention Time (HRT) was observed.